Identifikasi Mikroplastik pada Air Sumur Gali di sekitar TPA Piyungan Yogyakarta - Utami, Inggita; Liani, Myda (Jurnal Riset Daerah, 2021)
Microplastics measuring less than 5 mm can potentially contaminate groundwater around landfills. Many residents around the Piyungan Landfills use dug well water to meet their needs and threaten their health if it accumulates in the body. This study analyzes the abundance and microplastic polymers in well water around the Piyungan landfill. Data collection was carried out in January 2021 on three dug wells at a distance of 0-1 km, 1-2 km, and 2-3 km to the northwest and north of the Piyungan landfill. Nine water samples from each well were taken with intervals of collection in the morning and evening. The following steps include sample screening, sample drying, density separation, sample heating, microplastic separation, microplastic abundance calculation, and polymer type analysis. The results of the study found that the highest microplastic was 146 ± 109 particles/L in wells with a distance of 0-1 km, followed by wells at a distance of 1-2 km with an abundance of microplastics of 116 ± 31 particles/L and the lowest was in wells with a distance of 2-3 km with an abundance of microplastics of 77 ± 23 particles/L. Based on the Kruskal Wallis test results, it was concluded that the difference in the distance between the wells from the Piyungan landfill affected the abundance of microplastics. The types of microplastic polymers identified at three dug wells locations are Polystyrene (PS) and Polyvinyl Chloride (PVC) polymers. This study concludes that microplastics were found in all water samples in dug wells around Piyungan landfill with the highest number in wells with a distance of 0-1 km, and the types of polymers identified were PS and PVC.